2015
DOI: 10.1007/s10008-015-2884-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure and composition effects on electrochemical reduction of carbon dioxide

Abstract: Carbon dioxide electrochemical reduction has attracted significant attention due to its great potential in environmental protection and energy storage. In this mini-review, some recent progress in heterogeneous electrochemical reduction of carbon dioxide is summarized, with a particular emphasis on the effects of catalyst surface modification. Several structural (metal overlayers, particle size adjustment, roughness creation, special 2D or 3D structure patterning) and compositional (alloy, doping, oxide, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 77 publications
0
31
0
Order By: Relevance
“…In addition, the onset potential of CO 2 reduction on porous Ag electrode was about 0.15 V less in comparison with the Ag foil electrode. Both the lower overpotential and increased CO partial current density could be attributed to the large active surface area of the porous electrode [11]. Furthermore, it is presumed that the higher activity may be due to the greater stabilization of CO 2 À intermediates on the highly roughed surface, resulting in smaller overpotential needed to overcome the thermodynamic barrier.…”
Section: Cyclic Voltammetry Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the onset potential of CO 2 reduction on porous Ag electrode was about 0.15 V less in comparison with the Ag foil electrode. Both the lower overpotential and increased CO partial current density could be attributed to the large active surface area of the porous electrode [11]. Furthermore, it is presumed that the higher activity may be due to the greater stabilization of CO 2 À intermediates on the highly roughed surface, resulting in smaller overpotential needed to overcome the thermodynamic barrier.…”
Section: Cyclic Voltammetry Measurementsmentioning
confidence: 98%
“…In addition, nanostructured electrocatalysts have been shown to improve catalytic stability. Moreover, a large portion of low-coordinated sites on nanostructured surface make the catalytic behavior different from flat surface in corresponding bulk metals [10,11]. The unique properties have shown in oxygen reduction reaction (ORR) [12], hydrogen evolution reaction (HER) [13] and oxygen evolution reaction (OER) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic behaviors of such nanolayers can be drastically changed due to the effects of the lattice strain and layer-substrate electron interaction [45]. Reske et al investigated the performance of Cu overlayers with different thicknesses ranging from 1 monolayer to 15 nm supported on a polycrystalline Pt substrate [62].…”
Section: Metal Catalysts (Cu and Zn)mentioning
confidence: 99%
“…Although several review articles related to CO 2 reduction have been published, nonprecious metal catalysts have not been systematically discussed [39][40][41][42][43][44][45]. Less expensive and environmentally friendly materials such as Cu, Zn, Sn, Bi, Co, carbons, and organic frameworks have demonstrated promise for the reduction of CO 2 to hydrocarbons, formic acid, and CO.…”
Section: Introductionmentioning
confidence: 97%
“…Due to existence of two strong C=O bonds in the CO 2 molecule, its electroreduction requires high overpotentials, and the low reaction efficiency still remains fundamental problem limiting practical applications. [1][2][3] During recent years, various catalysts, including noble and non-noble transition metals, as well as their numerous coordination compounds, have been considered as catalysts for CO 2 electroreduction. [4][5][6][7][8][9][10] It has been demonstrated that selectivity of the process depends largely on the activating adsorptive (CO 2 ) phenomena and the affinity of catalytic centers to adsorbed carbon monoxide intermediate.…”
mentioning
confidence: 99%